Post hoc analysis of a randomized placebo-controlled trial suggests potential visual benefits of branched-chain amino acids in retinitis pigmentosa - Tomoko Hasegawa; Hanako Ohashi Ikeda; Hiroyasu Abe; Yoko Amino; Takayuki Nakagawa; Harue Tada; Manabu Miyata; Akio Oishi; Satoshi Morita; Akitaka Tsujikawa (Scientific Reports)
Abstract This study assessed and compensated for baseline differences in a randomized clinical trial of branched-chain amino acids (BCAAs) in patients with retinitis pigmentosa (RP). Seventy patients with eyes showing a mean deviation (MD) of − 5.0 to − 25.0 dB in the Humphrey visual-field (HFA 10-2) test were included. Participants were administered BCAAs (TK-98) or a placebo for 78 weeks. We evaluated the reliability of the baseline screening HFA test, analyzed HFA data from 13 weeks after treatment initiation, and conducted a covariate-adjusted analysis. Eyes showed paradoxical improvement as the start of the clinical trial approached. The proportion of eyes demonstrating visual-field improvement in the eligibility screening test was higher in the TK-98 group than in the placebo group. Analysis of HFA 10-2 data from 13 weeks post-treatment, excluding screening data, showed slower decrease rates of total point score (TPS) and MD in the TK-98 group. After covariate adjustment, TPS and MD reductions tended to be slower in the TK-98 group than in the placebo group. The eligibility screening visual-field test could be affected by psychological factors, such as patients’ concentration or motivation, leading to better-than-usual screening test results and making them less appropriate as baseline data.